2006
DOI: 10.1681/asn.2006060677
|View full text |Cite
|
Sign up to set email alerts
|

Discoidin Domain Receptor 1 Null Mice Are Protected against Hypertension-Induced Renal Disease

Abstract: A frequent complication of hypertension is the development of chronic renal failure. This pathology usually is initiated by inflammatory events and is characterized by the abnormal accumulation of collagens within the renal tissue. The purpose of this study was to investigate the role of discoidin domain receptor 1 (DDR1), a nonintegrin collagen receptor that displays tyrosine-kinase activity, in the development of renal fibrosis. To this end, hypertension was induced with angiotensin in mice that were genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
110
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 24 publications
9
110
1
1
Order By: Relevance
“…11 This study revealed reduced renal inflammation in the transgenic mice, which suggests indirect consequences of DDR1 activation on the progression of renal fibrosis through enhanced local inflammation. Such a protective effect of DDR1 deletion secondary to its antiinflammatory effect has been also demonstrated in a model of atherosclerosis in mice.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…11 This study revealed reduced renal inflammation in the transgenic mice, which suggests indirect consequences of DDR1 activation on the progression of renal fibrosis through enhanced local inflammation. Such a protective effect of DDR1 deletion secondary to its antiinflammatory effect has been also demonstrated in a model of atherosclerosis in mice.…”
Section: Discussionmentioning
confidence: 60%
“…We have previously shown that DDR1-deficient mice and WT counterparts present no quantitative difference in circulating leukocytes, lymphocytes, monocytes, and neutrophils. 11 Here, we have found that a subset of the interstitial leukocytes recruited after UUO expressed DDR1. Because DDR1-null mice presented reduced inflammation in the obstructed kidney, we next addressed the issue of a proinflammatory role of DDR1 in macrophages via increased migration or differential M1/M2 polarization.…”
Section: Macrophages Isolated From Ddr1-null Mice Present Reduced Migmentioning
confidence: 69%
See 3 more Smart Citations